Design and synthesis of new non nucleoside inhibitors of DNMT3A. Issue 17 (1st September 2015) - Erdmann, Alexandre; Menon, Yoann; Gros, Christina; Molinier, Nicolas; Novosad, Natacha; Samson, Arnaud; Gregoire, Jean-Marc; Long, Christophe; Ausseil, Frédéric; Halby, Ludovic; Arimondo, Paola B.
Graphical abstract: Abstract: DNA methylation, an epigenetic modification regulating gene expression, is a promising target in cancer. In an effort to identify new non nucleosidic inhibitors of DNA methyltransferases, the enzymes responsible for DNA methylation, we carried out a high-throughput screening of 66, 000 chemical compounds based on an enzymatic assay against catalytic DNMT3A. A family of propiophenone derivatives was identified. After chemical optimization and structure activity relationship studies, a new inhibitor (33 ) was obtained with an EC50 of 2.1 μM against DNMT3A. The mechanism of inhibition of the compound was investigated as it forms a reactive Michael acceptor group in situ. Thereby, the Michael acceptor 20 was identified. This compound was further characterized for its biological activity in cancer cells.